1976
DOI: 10.1210/endo-99-3-793
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D and Its Metabolites on Calcium Transport in the Diabetic Rat

Abstract: We studied diabetic rats, 5 days after streptozotocin injection, and matched controls to determine whether depressed duodenal calcium absorption associated with uncontrolled diabetes in the rat would respond to vitamin D or its metabolites. At the appropriate time following the intravenous injection of 0.25 mug of either vitamin D3, 25-hydroxycholecalciferol (25-OHD3), 1,25-dihydroxycholecalciferol (1,25-OH)2D3), or 1alpha-hydroxycholecalciferol (1alpha-OHD3) to half of each diabetic and control group, calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…However, it has not yet been clearly determined why diabetes mellitus causes a reduction in bone mass. Schneider et al [25] and Spencer [26] observed depressed Ca resorption from the intestine, reduction of Ca-binding protein activity, increase in serum PTH level, and decrease in renal 25-hydroxyvitamin D-l-hydroxylase activity in diabetes mellitus. In the current study, STZ-induced diabetes mellitus showed osteoporosis, confirmed by reductions in dry weight, ash weight, and calcium and phosphoros content of the femurs, and of bone volume in bone histomorphometry of the tibias.…”
Section: Discussionmentioning
confidence: 97%
“…However, it has not yet been clearly determined why diabetes mellitus causes a reduction in bone mass. Schneider et al [25] and Spencer [26] observed depressed Ca resorption from the intestine, reduction of Ca-binding protein activity, increase in serum PTH level, and decrease in renal 25-hydroxyvitamin D-l-hydroxylase activity in diabetes mellitus. In the current study, STZ-induced diabetes mellitus showed osteoporosis, confirmed by reductions in dry weight, ash weight, and calcium and phosphoros content of the femurs, and of bone volume in bone histomorphometry of the tibias.…”
Section: Discussionmentioning
confidence: 97%
“…Dia betic rats show other evidence for vitamin D deficiency including decreased duodenal [3,15,16] and cecal and colonic [9] calcium transport in comparison with controls. The depression of calcium transport in diabetes is also the result of deficiency of l,25-(OH)2D since the transport defect is corrected by ad ministration of l,25-(OH)2D [17], and by in sulin treatment [16], which restores 1,25-(OH)2D to normal in diabetes [1], Based on our previous study of vitamin D metabolites in diabetes [1], the present study shows that CaBP of cecum and colon re sponds to lower levels of serum 1,25-dihydroxyvitamin D in the diabetic state. The depression is not as great as in duodenum where CaBP specific activity at 5 days of dia betes is one-third that of controls [4], At 12 days of diabetes, growth of cecum overcomes the depressed CaBP per unit of mucosa to nearly maintain total activity, while colonic CaBP of diabetes remains depressed in both total and specific activity.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of insulin led to hypercalciuria Schedl, 1972 andSchneider et al, 1976) which has been felt to result from osmotic diuresis caused by glycosuria (Massry et al, 1973 andMonnier et al, 1978). Increased urinary calcium excretion may be one possible cause of negative calcium balance in diabetes (Wood et al, 1984).…”
Section: Endocrinolmentioning
confidence: 99%
“…Disturbances in calcium metabolism which have been demonstrated in both experimental insulin-deficient rats (Ramamurthy et al, 1973;Schedl et al, 1978;Hough et al, 1982 andWongsurawat et al, 1983) and diabetic patients (Fogh-Andersen et al, 1982 and have been attributed to the decrease in levels of 25(OH)D and 24, 25(OH)2D (Ishida et al, 1983(Ishida et al, , 1985 and impairment of renal, 1, 25(OH)2D3 production (Schneider et al, 1976;1977a andWongsurawat et al, 1983). Such long term disturbances may result in negative calcium balance which can be reversed by insulin treatment.…”
mentioning
confidence: 99%